Intrapersonal Communication And Buddhist Perspective Meditation - *, Marjianto (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to explain the importance of intrapersonal communication, meditation and relation among meditation towards personal. If the relation among intrapersonal communication and meditation trully give effect towards personal, so meditation practice should be taught and developed in the society. This research used qualitative approach. by using qualitative approach so the data will be obtained completely, deeper, credible and meaningful so that the objective of the research can be achieved. Besides the problems in this research appropriately are solved by qualitative approach. The result of this research shows that there ere lots of people who do not know that intrapersonal communication happens in themselves. They only know that intrapersonal communication happens only among themselves and others. The activites of intrapersonal communication that are done in the daily activity such as: praying, gratitude, reflection, etc. One should be able to cummunicate to himself, it is because it will help them to recognize himself, to know the strength and weakness, so that he can be aware of himself. Meditation is a communication intrapersonal activity, it is because by meditating some one can concentrate on his mind, either through mind or body. Meditation trully give effect towards personal character.